Use of Atypical Antipsychotics in Nursing Homes and Pharmaceutical Marketing. Issue 2 (February 2015) - Pimentel, Camilla B.; Donovan, Jennifer L.; Field, Terry S.; Gurwitz, Jerry H.; Harrold, Leslie R.; Kanaan, Abir O.; Lemay, Celeste A.; Mazor, Kathleen M.; Tjia, Jennifer; Briesacher, Becky A.
<x xml:space="preserve">Abstract</x> Objectives To describe the current extent and type of pharmaceutical marketing in nursing homes (NHs) in one state and to provide preliminary evidence for the potential influence of pharmaceutical marketing on the use of atypical antipsychotics in NHs. Design Nested mixed‐methods, cross‐sectional study of NHs in a cluster randomized trial. Setting Forty‐one NHs in Connecticut. Participants NH administrators, directors of nursing, and medical directors (n = 93, response rate 75.6%). Measurements Quantitative data, including prescription drug dispensing data (September 2009–August 2010) linked with Nursing Home Compare data (April 2011), were used to determine facility‐level prevalence of atypical antipsychotic use, facility‐level characteristics, NH staffing, and NH quality. Qualitative data, including semistructured interviews and surveys of NH leaders conducted in the first quarter of 2011, were used to determine encounters with pharmaceutical marketing. Results Leadership at 46.3% of NHs (n = 19) reported pharmaceutical marketing encounters, consisting of educational training, written and Internet‐based materials, and sponsored training. No association was detected between level of atypical antipsychotic prescribing and reports of any pharmaceutical marketing by at least one NH leader. Conclusion NH leaders frequently encounter pharmaceutical marketing through a variety of ways, although the impact on atypical antipsychotic prescribing is unclear.